How AI-generated images impact consumer perceptions and brand identity - Nazrin, Nizar; Isahak Merican, Farah Merican; Taharuddin, Nurul Shima; Ibrahim, Nor Idayu (Universiti Teknologi MARA, Perak, 2025)
This conceptual paper explores the impact of AI-generated images on consumer perceptions and brand identity within the advertising sector. Leveraging a comprehensive review of recent literature and theoretical frameworks, the study synthesizes insights on the advantages and challenges associated with AI-generated visuals. Findings indicate that while AI-generated images offer significant opportunities for personalization and creativity, they also present challenges related to authenticity, emotional engagement, and brand consistency. Specifically, AI-generated imagery can enhance visual appeal but may undermine perceived authenticity, affecting consumer trust. Emotional engagement with AI- generated content varies, with some consumers experiencing a disconnect due to the artificial nature of the visuals. Additionally, maintaining brand identity is critical, as AI-generated images can either support or disrupt brand coherence depending on their alignment with established brand values. The paper applies theories such as the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB) to understand consumer attitudes towards AI technology. The discussion provides recommendations for advertisers to balance innovation with authenticity, enhance emotional resonance, and ensure consistency in brand messaging. Future research is suggested to empirically validate these conceptual insights and further explore the impact of AI-generated imagery on consumer behavior and brand performance.